Deciphering the effects of antibiotics on nitrogen removal and bacterial communities of autotrophic denitrification systems in a three-dimensional biofilm electrode reactor. (15th December 2022) - Sun, Qi; Zhu, Guangcan
Abstract: In this study, three-dimensional biofilm electrode reactors (3D-BERs) were constructed, and the effects of metronidazole (MNZ) on the nitrogen removal performance and bacterial communities of autotrophic denitrification systems were evaluated. The results showed that nitrogen removal decreased slightly as the MNZ concentration increased. Specifically, nitrate-nitrogen removal efficiency decreased from 97.98% to 89.39%, 86.93%, 82.64%, and 82.77% within 12 h after the addition of 1, 3, 5, and 10 mg/L MNZ, respectively. The 3D-BERs showed excellent MNZ degradation ability, especially at a concentration of 10 mg/L. The MNZ removal efficiency could be as high as 94.38% within 6 h, and the average removal rate increased as the MNZ concentration increased. High-throughput sequencing results showed significant changes in the bacterial community under different MNZ concentrations. As the antibiotic concentration increased, the relative abundances of Hydrogenophaga and Silanimonas increased, from only 0.09% and 0.01% without antibiotics to 3.55% and 2.35%, respectively, at an antibiotic concentration of 10 mg/L. Changes in antibiotic concentration altered the abundances of genes involved in nitrogen metabolism. Redundancy analysis showed that MNZ removal efficiency was positively correlated with SBR1031, SC-I-84, Hydrogenophaga, Silanimonas and Denitratesoma, whereas the removal efficiencies of nitrate-nitrogen and total nitrogen were negatively correlated with these genera. The results of this study provide a theoretical basis for studying the toxic effects of antibiotics on the denitrification process and also provide guidance for the control of antibiotics and nitrogen pollution in ecosystems. Graphical abstract: Image 1 Highlights: Nitrogen removal decreased slightly with increase in MNZ concentration in 3D-BER. MNZ removal efficiency is as high as 94.38% even at a higher concentration of 10 mg/L. There is a good linear relationship between MNZ concentration and average removal rate. Relative abundances of Hydrogenophaga and Silanimonas increased obviously.